TEKNOLOGI 3D PRINTING DALAM INDUSTRI KONSTRUKSI - Suharto, Sunaryo Wongso; Firman Sarifudin; Jin Oei, Fuk (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2024)
This research is an important review in the context of the development of 3D printing technology in the construction industry. Some key points to take away from the research include a clear recognition of the impact of 3D printing technology on architecture, noting that this technology has opened up new opportunities in terms of design complexity, detail and materiality that were previously impossible to achieve. This research uses a systematic approach in reviewing literature related to 3D printing technology in the construction industry. Data was used to search for journal articles with Publish or Perish starting from 2014-present, in order to ensure diversity of data sources. The use of bibliometric analysis (VOSviewer) helps in identifying the main trends in research on 3D printing in the construction industry. This includes the annual number of articles, prominent authors, and co-author networks. This analysis helps provide an overview of developments and collaborations in this field.Content analysis of selected articles provides further insight into specific themes discussed in this literature, to understand the context and trends within the topic in greater depth. Categorize 3D printing technologies in architecture based on system scale. This classification makes it possible to understand the various technical aspects involved. Outlines the challenges faced and future directions in 3D printing research in architecture. This is important to help guide further research and innovation in the construction industry. Thus, this research provides a comprehensive view of the latest developments in 3D printing technology in the construction industry and can be a valuable source of information for professionals and researchers in this field. In addition, bibliometric analysis and content analysis help identify important trends and themes in the literature, which can guide future research and development in this field. Abstrak Penelitian ini merupakan tinjauan penting dalam konteks perkembangan teknologi 3D printing pada industri konstruksi. Beberapa poin penting yang dapat diambil dari penelitian ini termasuk pengakuan yang jelas terhadap dampak teknologi 3D printing terhadap arsitektur, mengingat bahwa teknologi ini telah membuka peluang baru dalam hal kompleksitas desain, detail, dan materialitas yang sebelumnya tidak mungkin dicapai. Penelitian ini menggunakan pendekatan sistematis dalam mengkaji literatur terkait teknologi 3D printing pada industri konstruksi. Data digunakan untuk pencarian artikel jurnal dengan Publish or Perish mulai tahun 2014-sekarang, guna menjamin keberagaman sumber data. Penggunaan analisis bibliometrik (VOSviewer) membantu dalam mengidentifikasi tren utama dalam penelitian 3D printing di industri konstruksi. Ini termasuk jumlah artikel tahunan, penulis terkemuka, dan jaringan rekan penulis. Analisis ini membantu memberikan gambaran perkembangan dan kolaborasi di bidang ini. Analisis isi artikel terpilih memberikan wawasan lebih lanjut mengenai tema spesifik yang dibahas dalam literatur ini, untuk memahami konteks dan tren dalam topik secara lebih mendalam. Kategorikan teknologi 3D printing dalam arsitektur berdasarkan skala sistem. Klasifikasi ini memungkinkan untuk memahami berbagai aspek teknis yang terlibat. Menguraikan tantangan yang dihadapi dan arah masa depan dalam penelitian 3D printing di bidang arsitektur. Hal ini penting untuk membantu memandu penelitian dan inovasi lebih lanjut dalam industri konstruksi. Dengan demikian, penelitian ini memberikan pandangan komprehensif tentang perkembangan terkini teknologi 3D printing di industri konstruksi dan dapat menjadi sumber informasi berharga bagi para profesional dan peneliti di bidang ini. Selain itu, analisis bibliometrik dan analisis isi membantu mengidentifikasi tren dan tema penting dalam literatur, yang dapat memandu penelitian dan pengembangan di masa depan di bidang ini.